Circulating 25-hydroxy-vitamin D and risk of cardiovascular disease - Wang, Lu; Song, Yiqing; Pilz, Stefan; März, Winfried (Circulation. Cardiovascular quality and outcomes, 2012)
Background—Vitamin D status has been linked to the risk of cardiovascular disease (CVD). However, the optimal 25-hydroxy-vitamin D (25[OH]-vitamin D) levels for potential cardiovascular health benefits remain unclear.Methods and Results—We searched MEDLINE and EMBASE from 1966 through February 2012 for prospective studies that assessed the association of 25(OH)-vitamin D concentrations with CVD risk. A total of 24 articles met our inclusion criteria, from which 19 independent studies with 6123 CVD cases in 65 994 participants were included for a meta-analysis. In a comparison of the lowest with the highest 25(OH)-vitamin D categories, the pooled relative risk was 1.52 (95% confidence interval, 1.30-1.77) for total CVD, 1.42 (95% confidence interval, 1.19-1.71) for CVD mortality, 1.38 (95% confidence interval, 1.21-1.57) for coronary heart disease, and 1.64 (95% confidence interval, 1.27-2.10) for stroke. These associations remained strong and significant when analyses were limited to studies that excluded participants with baseline CVD and were better controlled for season and confounding. We used a fractional polynomial spline regression analysis to assess the linearity of dose-response association between continuous 25(OH)-vitamin D and CVD risk. The CVD risk increased monotonically across decreasing 25(OH)-vitamin D below ≈60 nmol/L, with a relative risk of 1.03 (95% confidence interval, 1.00-1.06) per 25-nmol/L decrement in 25(OH)-vitamin D.Conclusions—This meta-analysis demonstrated a generally linear, inverse association between circulating 25(OH)-vitamin D ranging from 20 to 60 nmol/L and risk of CVD. Further research is needed to clarify the association of 25(OH)-vitamin D higher than 60 nmol/L with CVD risk and assess causality of the observed associations.
Gesehen am 08.05.2019